THE QUALITY AND TIMELINESS OF ISSUING FINANCIAL REPORTS IN LIGHT OF THE APPLICATION OF JOINT AUDITING- AN APPLIED STUDY IN A SAMPLE OF AUDITORS' OFFICES IN IRAQ - Hazem Ali Muttair (Journal Park Publishing, 2022)
The aim of this research is to show the impact of the application of joint auditing on the quality and timing of issuing reports in Iraq, By defining the concept of joint auditing and determining the positive and negative effects and the mechanisms to be applied and to explain the research problem and achieve its objectives, the descriptive analytical approach was adopted, as (90) questionnaires were distributed to the sample members, (Account auditors, bank employees, accountants) and the collected data were analyzed by means of a questionnaire using descriptive and analytical statistical methods, and using the statistical analysis program (SPSS). The research hypotheses were tested, and the research concluded: Preparing and adopting a local auditing standard for joint auditing from the relevant authorities in Iraq, regulating the audit process in terms of planning, organization, reporting, cooperation, coordination and communication between auditors. Encouraging companies to adopt joint auditing for the purpose of increasing the quality of reports and discovering errors and fundamental distortions after the success of the experience in the banking sector.
Keywords: joint auditing, financial reports, quality and timing of reports